ENUNCIATIVE-INTERATIONAL FRAMEWORK: A MULTIDIMENSIONAL APPROACH FOR THE ANALYSIS OF DIFFERENT TYPES OF TEXT - Paiva Brito, Mariza Angélica; Arruda Martins, Mayara (Revista de Letras, 2025)
With the advancement of digital interactions, the challenges for textual analysis have intensified, mainly in relation to redefining its analysis criteria in order to encompass these new interactions. In this new scene, characterized by the production and circulation of dynamic digital texts, especially on social networks, the need for an update in theoretical and methodological approaches to Textual Linguistics emerges. This article proposes a methodological framework for the analysis of technotexts, considering multisemiotic, technodiscursive and interactive aspects that shape textuality in the digital environment. Continuing the proposal of authors such as Cavalcante, Brito and Martins (2024) and Martins (2024), we investigated the enunciative, referential and argumentative relationships that constitute digital texts. The proposal is presented through an analytical tool that combines qualitative and quantitative methods, capable of exploring both the linguistic and multisemiotic elements of technotexts and the impact of digital ecosystems on language acts. The concrete examples discussed in this study illustrate the applicability of the approach, which integrate theory and practice, offering theoretical-methodological support for researchers and educators to face the complexities of contemporary textuality.